Pengembangan Ekonomi Kreatif di Pondok Pesantren Melalui Pemberdayaan Kewirausahaan Santri Menuju Era Digital 5.0 - Kholifatul Husna Asri (ALIF, 2022)
This study aims to determine how the development of the creative economy of Islamic boarding schools through the empowerment of student (santri) entrepreneurship towards the digital era 5.0. This research data analysis method uses descriptive qualitative analysis, namely to analyze qualitative data that is described through words or sentences to obtain a conclusion. The balance in era 5.0 provides graduates with successful and quality human resources (HR). Islamic boarding schools are not only religious-based educational institutions , but can be said as a place to give birth to a generation that has Islamic character and as an economic institution for the welfare of students and the community. Based on the results of the study, to prepare students who have expertise competence and entrepreneurial spirit, Islamic boarding schools take several approaches, including: (1) First, the pesantren curriculum, guidelines for teaching and learning activities in Islamic boarding schools, focusing on developing human resources (santri) through the provision of training, and entrepreneurship education. (2) Second, qualified teachers, Islamic boarding schools prepare teaching staff who have competence, expertise in their fields and experience, so that with the knowledge, skills possessed by teachers, they can encourage enthusiasm and provide direction to students, (3) Third, strategies or learning models that focus on the skill competence of students..